San Marino : Financial Sector Assessment Program-Detailed Assessment of Basel Core Principles for Effective Banking Supervision. (IMF Staff Country Reports; Country Report ;, 2010)
Based on the request of the Central Bank of San Marino (CBSM), an assessment of San Marino's compliance with the Basel Core Principles was undertaken in November 2009 in the context of the Financial Sector Assessment Program (FSAP). The mission followed the 2006 Core Principles methodology. The banking sector dominates the financial sector. San Marino's macroeconomic policy is generally sustainable. San Marino has engaged in a substantial economic reform effort since 2005 to increase market discipline. The CBSM should address governance issues in banks.